EFEKTIVITAS DAN KONTRIBUSI PAJAK BUMI DAN BANGUNAN PERDESAAN DAN PERKOTAAN TERHADAP PENDAPATAN ASLI DAERAH KABUPATEN PONOROGO - Ayu Permatasari; Galih Wicaksono (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2022)
This study aims to determine the effectiveness of Rural and Urban Land and Building Tax revenue (PBB-P2), as well as the contribution of PBB-P2 to Regional Original Income (PAD). This research is a type of quantitative descriptive research. The data collection technique was carried out using documentation techniques, and based on PBB-P2 and PAD data for Ponorogo Regency in 2018-2020. The results showed that the level of effectiveness of PBB-P2 on average was in the very effective criteria, while the level of contribution of PBB-P2 to PAD was still in the low criteria. Therefore, it is necessary to strengthen its potential so that its contribution can be even greater, so that PBB-P2 can become one of the mainstays for local governments in increasing PAD in Ponorogo Regency